Research in organizational change and development. - Shani, Abraham B. Rami; Noumair, Debra Ann (Research in organizational change and development ;, 2017)
2017 marks the silver anniversary of the Research in Organizational Change and Development series, founded in 1987 by Dick Woodman and Bill Pasmore, and currently edited by Rami Shani and Debra Noumair. This volume includes contributions from authors who have published in the first few volumes, contributions that examine the impact of the research published in the series on OD&C research, theoretical developments and practice. Highlights include contributions from Bill Pasmore and Dick Woodman as well as David Coghlan that focus on the essence and impact of the research reported in the last 24 volumes and possible research trajectories; Philip Mirvis and Mitchell Marks- the second recipients of the Pasmore-Woodman award (AOM 2016) on the highs and lows of co-researching; David Cooperrider on the evolution of Appreciative Inquiry since the foundation manuscript was published in ROCD Volume 1 (1987); Todd Jick & Kinthi Sturtevant who take stock of 30 years of change management, asking questions of and about its future and; Marvin Weisbord́s reflection on forty years of being a scholarly-practitioner in the field.